(3GdMQhH GdUdjHjI (B:s (3ceG QCgG GdYQH (B/s - (3eYdha(B. (3Cejf s ((3dHfGf(B;(3GdLRGFQ (B:s (3OGQ GdaGQGHj(B;(3GdeDSSI GdhWfjI ddGJUGd h GdfTQ ,s, 2001)
(3cGfJ GdMQhH GdUdjHjI h dGJRGd JTZd MjRG cHjQG ef GdcJGHGJ GdJGQjNjI aj GdTQb h GdZQH deG dgG ef Cf h NWQ Ydi GdUYO GdSjGSjI h GdGLJeGYjI h GdacQjI h GdGbJUGOjI h GdMVGQjIs
Keywords: (3GdYQHs; (3JGQjNs